2022
DOI: 10.3389/fsufs.2022.911199
|View full text |Cite
|
Sign up to set email alerts
|

Soil bacterial community response to cover crops, cover crop termination, and predicted climate conditions in a dryland cropping system

Abstract: Soil microbial communities are integral to highly complex soil environments, responding to changes in aboveground plant biodiversity, influencing physical soil structure, driving nutrient cycling, and promoting both plant growth and disease suppression. Cover crops can improve soil health, but little is known about their effects on soil microbial community composition in semiarid cropping systems, which are rapidly becoming warmer and drier due to climate change. This study focused on a wheat-cover crop rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Amplicon sequencing analysis did not reveal significant beta diversity changes in the bacterial community of the sunflower rhizosphere, mirroring findings from Morales et al (2022) and Ouverson et al (2022) . Despite the lack of significant structural changes, treatment effects on community composition were evident, underscoring the sensitivity of compositional metrics over beta diversity in capturing microbial response to agricultural interventions.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Amplicon sequencing analysis did not reveal significant beta diversity changes in the bacterial community of the sunflower rhizosphere, mirroring findings from Morales et al (2022) and Ouverson et al (2022) . Despite the lack of significant structural changes, treatment effects on community composition were evident, underscoring the sensitivity of compositional metrics over beta diversity in capturing microbial response to agricultural interventions.…”
Section: Discussionmentioning
confidence: 50%
“…However, an increase in Pielou's evenness index for sunflowers cultivated after winter CC suppression, regardless of the suppression method, suggests a more balanced and diverse bacterial community, akin to observations by Li et al (2023) under a rye (Secale cereale L.) cover crop system. Amplicon sequencing analysis did not reveal significant beta diversity changes in the bacterial community of the sunflower rhizosphere, mirroring findings from Morales et al (2022) and Ouverson et al (2022). Despite the lack of significant structural changes, treatment effects on community composition were evident, underscoring the sensitivity of compositional metrics over beta diversity in capturing microbial response to agricultural interventions.…”
Section: Discussionmentioning
confidence: 69%
“…warm season cover crop Treatments (Table 3). In contrast, we previously found that under the cover crop phase of the wheatcover crop rotation, cover crops had significant differences in four of the eight most abundant phyla when compared to fallow (Ouverson et al, 2022). This suggests that cover crops may have transient effects on the structure of the soil microbial community and these effects may no longer be apparent under the subsequent cash crop.…”
Section: Discussionmentioning
confidence: 71%
“…However, an increase in Pielou's evenness index for sunflowers cultivated after winter CC suppression, regardless of the suppression method, suggests a more balanced and diverse bacterial community, akin to observations by Li et al (2023) under a rye (Secale cereale L.) cover crop system. Amplicon sequencing analysis did not reveal significant beta diversity changes in the bacterial community of the sunflower rhizosphere, mirroring findings from Morales et al (2022) and Ouverson et al (2022). Despite the lack of significant structural changes, treatment effects on community composition were evident, underscoring the sensitivity of compositional metrics over beta diversity in capturing microbial response to agricultural interventions.…”
Section: Discussionmentioning
confidence: 69%